1999
DOI: 10.1590/s0100-879x1999000600012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aluminum sulfate on delta-aminolevulinate dehydratase from kidney, brain, and liver of adult mice

Abstract: The purpose of the present study was to investigate the in vitro and in vivo effects of aluminum sulfate on delta-aminolevulinic acid dehydratase (ALA-D) activity from the brain, liver and kidney of adult mice (Swiss albine). In vitro experiments showed that the aluminum sulfate concentration needed to inhibit the enzyme activity was 1.0-5.0 mM (N = 3) in brain, 4.0-5.0 mM (N = 3) in liver and 0.0-5.0 mM (N = 3) in kidney. The in vivo experiments were performed on three groups for one month: 1) control animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…It has been reported that acute intraperitoneal administration of aluminum induces a temporal diminution of GSH in liver, increases hemooxygenase activity with reduction of cytochrome P450 and, later, an increase in LPO (Jeffery et al 1996). Other authors indicated that aluminum accumulation in liver was accompanied by a decreased GSH level and in a decrease in glutathione peroxidase (El-Maraghy et al 2001), while, in adult mice, exposure to aluminum was proved to inhibit d-aminolevulinate dehydratase activity of kidneys (Schetinger et al 1999). Data described in this work do not allow us to determine the order of development of the events studied.…”
Section: Parametermentioning
confidence: 56%
“…It has been reported that acute intraperitoneal administration of aluminum induces a temporal diminution of GSH in liver, increases hemooxygenase activity with reduction of cytochrome P450 and, later, an increase in LPO (Jeffery et al 1996). Other authors indicated that aluminum accumulation in liver was accompanied by a decreased GSH level and in a decrease in glutathione peroxidase (El-Maraghy et al 2001), while, in adult mice, exposure to aluminum was proved to inhibit d-aminolevulinate dehydratase activity of kidneys (Schetinger et al 1999). Data described in this work do not allow us to determine the order of development of the events studied.…”
Section: Parametermentioning
confidence: 56%
“…The animals were euthanized 24 h after the last dose and the brains were dissected and collected immediately in beakers and maintained on ice (58C). The citrate was used to increase the aluminum absorption [22], probably by enhancing Al solubility [23]. The weight of the animals was monitored weekly, but no significant change was observed between the different groups during treatment (data not shown).…”
Section: Treatmentmentioning
confidence: 99%
“…Citrate was used because it increases Al absorption [27,28], probably by enhancing Al solubility [22].…”
Section: Treatmentmentioning
confidence: 99%